Critical closing pressure in cerebrovascular circulation. Issue 5 (1st May 1999) - Czosnyka, Marek; Smielewski, Piotr; Piechnik, Stefan; Al-Rawi, Pippa G; Kirkpatrick, Peter J; Matta, Basil F; Pickard, John D
Abstract : OBJECTIVE: Cerebral critical closing pressure (CCP) has been defined as an arterial pressure threshold below which arterial vessels collapse. Hypothetically this is equal to intracranial pressure (ICP) plus the contribution from the active tone of cerebral arterial smooth muscle. The correlation of CCP with ICP, cerebral autoregulation, and other clinical and haemodynamic modalities in patients with head injury was evaluated. METHOD: intracranial pressure, arterial blood pressure (ABP) and middle cerebral artery blood flow velocity were recorded daily in ventilated patients. Waveforms were processed to calculate CCP, the transcranial Doppler-derived cerebral autoregulation index (Mx), mean arterial pressure (ABP), intracranial pressure (ICP), and cerebral perfusion pressure (CPP). RESULTS: Critical closing pressure reflected the time related changes in ICP during plateau and B waves. Overall correlation between CCP and ICP was mild but significant ( R =0.41; p<0.0002). The mean difference between ABP and CCP correlated with CPP ( R =0.57, 95% confidence interval (95% CI) for prediction 25 mm Hg). The difference between CCP and ICP, described previously as proportional to arterial wall tension, correlated with the index of cerebral autoregulation Mx (p<0.0002) and CPP (p<0.0001). However, by contrast with the Mx index, CCP-ICP was not significantly correlated with outcome after head injury. CONCLUSION: Critical closing pressure, although sensitive to variations in ICP and CPP, cannot be used as an accurate estimator of these modalities with acceptable confidence intervals. The difference CCP−ICP significantly correlates with cerebral autoregulation, but it lacks the power to predict outcome after head injury.